An Ontological Security Analysis of Americanism in Turkish Foreign Policy, 1945-1960 - Alp, Emine (My University, 2023)
This article aims to draw attention to an aspect of Turkish foreign policy that has not been sufficiently theorized, especially within the framework of Ontological Security Theory. It attempts to show that one of the motives of Turkish foreign policy for its increasing orientation towards the West in the early Cold War period was to complete the three -centurylong project of Westernization and to find a relevant place in the international system. As an alternative version to the European model of Westernism or modernization, Americanism in Turkish foreign policy appeared as an illustration of the ontological security concerns of the country alongside its political, economic, and security interests. Under the Western security umbrella, the Turkish state sought not only to protect its territory from the Soviet threat but also to secure its state identity as an important part of Western civilization. Accordingly, T & uuml;rkiye adopted an anti-Soviet stance and tried to secure its place in the Western bloc, but often acted in favor of the United States and against its own national interests. This attitude has implications for the Ontological Security approach, which interprets the irrational and identity -oriented behavior of the nation -states as an effort to maintain the security of their 'being.' Consequently, this study argues that the pursuit of ontological security was an important element of Turkish foreign policy during this period.

Bu makale, Türk dış politikasının, özellikle Ontolojik Güvenlik kavramı çerçevesinde, yeterince kuramsallaştırılmamış bir yönüne dikkat çekmeyi amaçlamaktadır. Türk dış politikasının Soğuk Savaş döneminin başlarında Batı’ya doğru artan yöneliminin nedenlerinden birinin üç yüzyıldır devam eden Batılılaşma veya modernleşme projesini tamamlamak ve uluslararası sistemde kendine uygun bir yer bulmak olduğunu göstermeye çalışmaktadır. Türk dış politikasında Amerikancılık, Batıcılığın Avrupa modeline alternatif bir versiyon olarak ülkenin siyasi, ekonomik ve güvenlik çıkarlarının yanı sıra ontolojik güvenlik kaygılarının da bir göstergesi olarak ortaya çıkmıştır. Zira Batı güvenlik şemsiyesi altında Türk devleti sadece topraklarını Sovyet tehdidinden korumayı değil, aynı zamanda Batı medeniyetinin önemli bir parçası olarak devlet kimliğini de güvence altına almayı amaçlamıştır. Bu doğrultuda Türkiye, Sovyet karşıtı bir tutum benimseyerek Batı bloğundaki yerini sağlamlaştırmaya çalışmış, ancak çoğu zaman ABD’nin lehine ve kendi ulusal çıkarlarının aleyhine hareket etmiştir. Bu tutum, devletlerin irrasyonel ve kimlik odaklı davranışlarını onların ‘varoluş’ güvenliğini sürdürme çabası olarak yorumlayan Ontolojik Güvenlik yaklaşımı için çıkarımlar sunuyor. Sonuç olarak, bu çalışma ontolojik güvenlik arayışının bu dönemde Türk dış politikasının önemli bir unsuru olduğunu savunmaktadır.
Türk Dış Politikasında Amerikancılığın Ontolojik Güvenlik Analizi, 1945-1960
Keywords: Turkish Foreign Policy; Ontological Security Theory; Americanism; Western Bloc; Türk Dış Politikası; Ontolojik Güvenlik Kuramı; Amerikancılık; Batı Bloku